Possible Association Between DHEA and PKCε in Hepatic Encephalopathy Amelioration: A Pilot Study - Di Cerbo, Alessandro; Roncati, Luca; Marini, Carlotta; Carnevale, Gianluca; Zavatti, Manuela; Avallone, Rossella; Corsi, Lorenzo (Frontiers in Veterinary Science, 2021)
Objective: Hepatic encephalopathy (HE) is a neuropsychiatric syndrome caused by liver failure and by an impaired neurotransmission and neurological function caused hyperammonemia (HA). HE, in turn, decreases the phosphorylation of Protein kinase C (PKC) contributing to the impairment of neuronal functions. Dehydroepiandrosterone (DHEA) exerts a neuroprotective effect by increasing the GABAergic tone through a GABAA receptors stimulation. Therefore, we investigated the protective effect of DHEA in an animal model of HE, and the possible modulation of PKC expression in different brain area. Methods: Fulminant hepatic failure was induced in 18 male, Sprague Dawley rats by i.p. administration of 3 g/kg D-Galactosamine and after 30 minutes a group of animals received a subcutaneous injection of 25 mg/Kg (DHEA) repeated twice a day (3 days). Exploratory behavior and general activity were evaluated 24 h and 48 h after the treatments by open field test. Then, brain cortex and cerebellum were used for immunoblotting analysis of PKC level. Results: DHEA administration showed a significant improvement of locomotor activity both 24 and 48 h after D-Galactosamine treatment (****P < 0.0001) but did not ameliorate the liver parenchymal degeneration. Western blot analysis revealed a reduced immunoreactivity of PKC (*P < 0.05) following D-galactosamine treatment in rat cortex and cerebellum. After the addition of DHEA, PKC increased in the cortex in comparison with D-galactosamine-treated (***P < 0.001) and control group (*P < 0.05), while in the cerebellum only decreased (*P < 0.05) with respect to the control group. PKC decreased after treatment with NH4Cl alone and in combination with DHEA both in cerebellum and cortex (****P < 0.0001). MTS assay demonstrated the synergistic neurotoxic action of NH4Cl and glutamate pretreatment in cerebellum and cortex along with an increased cell survival after DHEA pretreatment, which resulted significant only in the cerebellum (*P < 0.05). Conclusion: An association between the DHEA-mediated increase of PKCε expression and the improvement of comatose symptoms was observed. PKCε activation and expression in the brain could inhibit GABA-ergic tone counteracting HE symptoms. In addition, DHEA seemed to ameliorate the symptoms of HE and to increase the expression of PKC in cortex and cerebellum.